The oral resources in the study of sebatik society’s social history (malaysia-indonesia) between spatial and opportunity - Eko Prayitno Joko; Syahruddin Awang Ahmad; Md. Saffie Abdul Rahim; Ramli Dollah; Zaini Othman; Abdul Rahman Mad Ali@Abang; Junaidah Awang Jambol; Marja Azlima Omar (sciendo, 2023)
Although oral sources can allow historians to reconstruct the past, they are not properly utilized by those who study them. This matter is made worse when oral sources are considered a method of collecting less relevant sources in retelling historical events. Indeed, its presence as a source collection method not only has the potential to gather new facts that have not yet been documented but can also confirm document sources and act to straighten history regarding an event that has been too focused on the dominance of the political elite or contains factual inaccuracies. Therefore, based on the advantages of oral sources, this study seeks to elevate the position of oral sources as an authoritative method and source on par with document sources in history. The effort is made by highlighting the space and opportunities of oral sources in reconstructing the social history of the Sebatik community. In this regard, it was found that there is still much social history of the Sebatik community that is of national value that has not been documented and remains in the form of "collective memory." For this reason, the presence of oral sources can potentially document and preserve the social history of the Sebatik community using oral tradition and oral history methods. This situation proves that oral sources are not only necessary in the context of reconstructing the social history of the Sebatik community but should also be urgently and urgently needed.